Jorge Oteiza's Modernity and His Latin American Travels - Marina Pérez de Mendiola (Studies in 20th & 21st Century Literature, 2006)
Along with Eduardo Chillida, Jorge Oteiza is one of the best-known Basque sculptors of his generation. Although many scholars have written on Oteiza's significant contribution to the field of sculpture, and have analyzed his theories on the meaning of art, very few take into consideration Oteiza's 13 years in Latin America, much less acknowledge that these years had a decisive impact on his art and particularly on his critical essays and poetry. In this essay, I explore how Oteiza's stay in Latin America contributed to his reevaluation of the avant-garde movements in Europe and Latin America, and how it led him to redefine his relationship to progress, science, reason and nature, space and time, ethics, and national art. During the course of his interaction with Latin American artistic movements, Oteiza's thoughts on artistic singularity and universality matured, and he confirmed his strong sense of spirituality in order to liberate traditionally defined conceptual opposites such as the intellectual and the sacred from their teleological confinement.
Keywords: Eduardo Chillida; Jorge Oteiza; Basque; art theory; Latin America; avant-garde; spirituality; teleological